Analysis of Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (Study of Increasing the Value of Hat Products and Market Expansion in Punggul Village, Sidoarjo Regency): Analisis Undang-Undang Nomor 20 Tahun 2008 Tentang Usaha Mikro, Kecil dan Menengah (Studi Peningkatan Nilai Produk Topi dan Perluasan Pasar di Desa Punggul, Kab. Sidoarjo) - Hendra Sukmana; Fajar Muharram; Safirah Diah Prasiwi; M Alief A (Universitas Muhammadiyah Sidoarjo, 2023)
Law number 20 of 2008 concerning micro, small and medium enterprises (UMKM) stipulates that the empowerment of MSMEs in the village of Punggul is the responsibility of the Sidoarjo Regency Cooperative and MSME services. MSMEs have an important role for economic growth in Indonesia. The perpetrators of umkm hats in the village of Punggul have not been recorded as a whole and have experienced several obstacles in running the business. The important role of the Regional Government through the Office of Cooperatives and Micro Enterprises, the Office of Industry, and the District Trade Office is expected to be able to provide To strengthen the competitiveness of MSMEs in facing the global market is to improve product quality and standards, increase financial access, improve the quality of human resources and the entrepreneurial spirit of MSMEs, provide facilities SMEs related to access to information and promotions both domestically and abroad. Highlights: Legal Responsibility: Law No. 20/2008 designates the Department of Cooperatives and MSMEs in Sidoarjo District as responsible for empowering UMKMs in Punggul village, emphasizing the legal framework's role. Economic Significance: UMKMs are vital for Indonesia's economic growth, underscoring their pivotal role in the nation's economic landscape. Strengthening Competitiveness: To enhance UMKMs' global market competitiveness, measures such as product quality improvement, financial access, human capital development, and information/promotion support are essential.